Development of Voice Command Locking System for Security Application - Rosda, Khairunnisa; Alias, Afishah (Enhanced Knowledge in Sciences and Technology, 2023)
A voice command locking system that can transmit and receive signals when the users give a voice command using a key phrase to the system has been built. The motivation for this project due to, users always face the difficulty of their locking system can be accessed by unauthorized persons. Furthermore, the previous locking system (the traditional way) comes with a variety of inconveniences such as the key is need to be fitted into the keyhole to open the locking system making it difficult for the users to open the locking system when their hands are full or the key become rusty and taking a lot of time to open the locking system because of incompetence to fit the key into the keyhole. Therefore, the voice command locking system is built to improve or overcome flaws, especially for the users to be more alert in protecting their houses and belongings. The voice recognition module v3 is used as a microphone and used to record, and store the pre-recorded key phrase. The key phrases were trained and tested before being stored in the voice recognition module v3. The pre-recorded key phrase was compared with the key phrase inputted by the user. An Arduino board is the main component in this project that acts as a receiver and transmitter of data and commands to devices that are connected to it. From the result analysis, the rotation of the servo motors changes based on the similarity of the key phrase from the user’s command with the pre-recorded key phrase that has been stored in the voice recognition module v3. It shows that the servo motors rotated 180 degrees if the key phrases have a similarity and vice versa. The functionality of the system was also evaluated based on the 86 milliseconds it took for the servo motors to begin rotating after receiving the command of the key phrase. With this upgraded system, the users will be safer with their locking system from being accessed by an unauthorized person, and more convenient to use the locking system. Overall, the voice command locking system can function well.